Pengaruh Konsumsi Jadi dan Olahan terhadap Obesitas di Indonesia - Ramadhani, Ira Chinta; Djamaluddin, Sartika (Jurnal Informatika Ekonomi Bisnis, 2024)
Obesity begins to be experienced by households with high, middle and low incomes. The prevalence of obesity is increasing along with globalization which makes access to food easier and the price of processed food is cheap but has high calories. Most households use their income for food consumption. Therefore, consumption of processed and processed foods is closely related to the risk of obesity. In this study, we investigated the extent to which processed and processed consumption affects obesity in Indonesia using the Instrumental Variable Probit method. We found that processed and processed consumption had a positive and significant effect on the obesity probability of 0.756. The random effect test also shows that fast and processed consumption has a positive and significant effect on the probability of obesity, such as those who live in urban areas increase the probability of experiencing obesity. Another findings show that life style, medical history and insurance status also have positive effect on obesity.